A combination of absorption and enzymatic biodegradation: phenol elimination from aqueous and organic phase. Issue 5 (23rd February 2019) - Tandjaoui, Nassima; Abouseoud, Mahmoud; Couvert, Annabelle; Amrane, Abdeltif; Tassist, Amina
ABSTRACT: Peroxidase from Brassica rapa was immobilized as cross-linked enzyme aggregates (CLEAs) and used to treat air containing phenol as a model molecule of volatile organic compounds (VOCs). Prior to an enzymatic treatment, phenol was absorbed into an aqueous or organic phase (silicone oil) to reach concentrations ranging from 20 to 160 mg/L. The process was carried out by introducing a desired weighing of BRP-CLEAs into preparations and reaction was started by injecting H2 O2 solution to the medium. Optimization of the reaction conditions in the organic solvent revealed an optimal contact time of 60 min, 60 mg/L of phenol concentration and 3 mM H2 O2, leading to a maximum removal yield of 70% for 3.4 UI/mL of BRP-CLEAs. These results were compared to those obtained in an aqueous medium that showed 90% of degradation yield after 40 min in the following conditions, 90 mg/L of initial phenol amount, 2 mM of H2 O2 and 2.5 UI/mL of BRP-CLEAs. Parameters of the Michaelis–Menten model, Km and Vmax, were also determined for the reaction in both phases. Phenol removal by BRP-CLEAs in silicone oil succeeded with 70% of conversion yield. It is promising regarding the transposition of such enzymatic process to hydrophobic VOCs.